Assessments corporate securities - Nikitin, Mykhailo (Skhid, 2013)
The present work studies the peculiarities of corporate securities assessment and defines the best technique of calculation of eminent cost in respect to the peculiarities of corporate securities circulation at the domestic securities market. Besides, some recommendations for improving the corporate securities assessment are suggested.